Taste disorders in the elderly - Magdalena Sykuła; Aleksandra Stelmach; Monika Szacoń; Katarzyna Kuśmierz; Małgorzata Sutuła; Marcin Stanisław Rząca; Hanna Kachaniuk (Kazimierz Wielki University, 2017)
Introduction: Disorders of the sense of taste mainly affect the elderly. There are many factors that contribute to their development, including various types of chronic diseases, polypharmacy, and the use of stimulants. Taste impairments lead to improper nutritional behaviour in the elderly, which may cause deterioration of their health and reduce their quality of life.      Aim: The aim of the study was to estimate taste deficits in the elderly.     Method: The participants were 24 persons aged 70-86. Sample size was limited by the number of available professional taste test kits (for identification of the four basic gustatory qualities: sweet, salty, sour, and bitter). The respondents were assisted by a researcher to fill in a survey about their health status, eating habits, and subjective assessment of their taste function.      Results: Most of the elderly persons assessed their taste function as being good, and the rating increased with the age of the participants. However, the organoleptic test showed that taste identification became less accurate with age. The participants had the greatest trouble recognizing the salty (58%) and sour (79%) tastes and had much less difficulty identifying the sweet (96%) and bitter (92%) tastes. The subjects' perception of taste became less and less intense with age. Conclusions: • The seniors were the least likely to accurately recognize the salty taste. • With age, the accuracy of identification of sweet, sour, bitter and salty gustatory qualities became lower. • The positive subjective assessment of the taste function in the elderly did not go hand in hand with their actual taste perception, which declined with age. • The use of stimulants such as alcohol and tobacco, pharmacological treatment of chronic diseases, and use dental prostheses reduced the perceived intensity of taste. • The taste disorders observed among the elderly can lead to dietary mistakes and thus negatively affect their health.